Choosing the right mask for your Asian patient with sleep apnoea: A randomized, crossover trial of CPAP interfaces. Issue 3 (6th September 2018) - Goh, Ken Junyang; Soh, Rui Ya; Leow, Leong Chai; Toh, Song Tar; Song, Pei Rong; Hao, Ying; Lee, Ken Cheah Hooi; Tan, Gan Liang; Ong, Thun How
ABSTRACT: Background and objective: A major challenge with the treatment of obstructive sleep apnoea (OSA) is adherence to continuous positive airway pressure (CPAP) therapy. Mask tolerability is an important determinant of adherence, however evidence to guide selection of mask interfaces is lacking. Methods: We conducted a randomized crossover trial of mask interfaces in CPAP therapy for moderate‐to‐severe OSA to assess adherence and efficacy of CPAP therapy with nasal mask, nasal pillow and oronasal masks. Demographic data, Nasal Obstruction Symptom Evaluation (NOSE) scores and craniofacial measurements were also analysed for associations with adherence with oronasal masks. Results: Eighty‐five patients were included in the study (mean ± SD age: 46 ± 12 years; body mass index: 29.9 ± 5.6 kg/m 2 ; apnoea–hypopnoea index (AHI): 53.6 ± 24.0 events/h). Patients had better adherence with nasal masks (average night use: 3.96 ± 2.26 h/night) compared to oronasal masks (3.26 ± 2.18 h/night, P < 0.001) and nasal pillows (3.48 ± 2.20 h/night, P = 0.007). Residual AHI was higher with oronasal masks (7.2 ± 5.2) compared to nasal masks (4.0 ± 4.2, P < 0.001) and nasal pillows (4.1 ± 3.3, P < 0.001). Twenty‐two (25.9%) patients had the best adherence with oronasal masks (4.22 ± 2.14 vs 2.93 ± 2.12 h/night, P = 0.016). These patients had lower NOSE scores (15 (0–35) vs 40 (10–55), P = 0.024) and larger menton‐labrale inferioris/biocular width ratios (31 ± 3% vs 28 ± 4%, P = 0.019). Conclusion: Nasal masks are the preferred interface during CPAP initiation. Patients with less nasal obstruction and a proportionally increased chin‐lower lip distance to mid‐face width may have better CPAP adherence with an oronasal mask interface. Abstract : In this randomized crossover trial of mask interfaces in continuous positive airway pressure (CPAP) therapy for obstructive sleep apnoea (OSA), adherence was highest with nasal masks compared to oronasal masks and nasal pillows. Residual apnoea–hypopnoea index (AHI) was higher with an oronasal mask interface. Nasal masks should be the first‐line interface during CPAP initiation. Example of a CPAP therapy mask for patients with OSA. See related Editorial